(3JaSjQ GdHZhis - (3GdMSjf Hf eSYhO Hf eMeO GdaQGA, CHh eMeO , eMjj GdSfI,J (B510 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3hSejJ GdCLfGO Ch JGOkG dcKQI GdeVGQH GdJi cGfhG jVQHhfgG hjhJOhfgG ai CSaGQge s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3abGd eGdc aOGc CHj hCei bdJ hjMc jG GHG SajGf gPG hGddg QShd Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B259s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs